2016
DOI: 10.1016/j.ejor.2015.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural operational research: Towards a framework for understanding behaviour in OR interventions

Abstract: Stimulated by the growing interest in behavioural issues in the management sciences, research scholars have begun to address the implications of behavioural insights for Operational Research (OR). This current work reviews some foundational debates on the nature of OR to serve as a theoretical backdrop to orient a discussion on a behavioural perspective and OR. The paper addresses a specific research need by outlining that there is a distinct and complementary contribution of a behavioural perspective to OR. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 171 publications
(233 reference statements)
0
30
0
Order By: Relevance
“…Our framework contrasts with that proposed recently by White (2016), which is offered as a device for thinking about behaviour across a three-dimensional typology of OR interventions. This typology is derived from alternative configurations of the (discrete) values taken by the dimensions of 'OR user' (individual/group), 'issue divergence' (high/low), and 'model use' (instrumental/symbolic).…”
Section: An Integrative Framework To Study Behaviour In Ormentioning
confidence: 87%
“…Our framework contrasts with that proposed recently by White (2016), which is offered as a device for thinking about behaviour across a three-dimensional typology of OR interventions. This typology is derived from alternative configurations of the (discrete) values taken by the dimensions of 'OR user' (individual/group), 'issue divergence' (high/low), and 'model use' (instrumental/symbolic).…”
Section: An Integrative Framework To Study Behaviour In Ormentioning
confidence: 87%
“…In addressing the above, OR scholars have, however, tended to highlight how much attention is paid to what people can't do rather than their capabilities (Phillips, 1984), and there has been a tendency to focus on individual behaviours rather than collective ones (White, 2016). In a social purpose context, individual capabilities may be insufficient to produce change, whereas it is suggested that collective capabilities are often necessary to achieve changes to broader complex societal problems (De Tombe, 2001).…”
Section: Applying the Capability Approach To Social Purpose Organisatmentioning
confidence: 99%
“…However, the outcome of collective action is greatly influenced by social structures, as they can enhance or restrain the exercise of agency (White & Bourne, 2006). Thus, appraising collective capabilities requires an analysis of the types of capabilities promoted through group membership as well as the ways in which social arrangements or social network relationships enable or disable collective action (White, 2016).…”
Section: Applying the Capability Approach To Social Purpose Organisatmentioning
confidence: 99%
“…The BOR research agenda revolves around questions as 'what are the consequences of humans being involved in OR', and 'what is the human impact on the OR process' (Hämäläinen et al 2013)? Behavioral mechanisms have important implications for the process, models, and outcomes of OR efforts (White 2016). In addition, behavioral mechanisms are one of the elements of the problems that OR projects aim to study (e.g.…”
Section: Introductionmentioning
confidence: 99%